Production, quality control and clinical applications of radiosynovectomy agents. (IAEA radioisotopes and radiopharmaceuticals reports, 2021)
"Therapeutic radiopharmaceuticals play a major role in today's nuclear medicine with a positive impact on the diagnosis and treatment of diseases. One area of application is radiation synovectomy (RSV). Previously, RSV agents were often simple colloids. More recently, matrixes labelled with short/medium range beta emitters have been developed. However, the lack of generic and peer-reviewed production, quality control as well as clinical application guidelines and recommendations, are a major concern for their application in patients. This publication presents recommendations and suggestions for production, quality control and quality assurance procedures for Member State laboratories in charge of radiopharmaceutical production, with a focus on the latest RSV agents. It also proposes standard operating procedures for RSV application in patients. The publication aims to assist both newcomers and those currently working in the field in establishing comparable levels of control."--Publisher's description.